Bacterial Contamination of Contact Lenses Among Some Female Students and Employee of College of Education-Ibn AIÂ Haitham, University of Baghdad - Ibrahim, I. A-J; A L- Hadaria, S. A. M.; Fayidh, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
During the last few yt:ars, au increase :n ut ilization   of contact  ienses (both  cosmetic and correction of refractive errors lenses) was noticed among  yotmg females, with an increase in eye infections.  The present i nvocation  was carried  out  to demonstrate  the percentage  of bacter ial contamination  of both the preservation  fluid and lens oonlainers. FiftyÂ two contact lenses users among  female students and em I ployees ofcollege   of  Education-Ibn  Al-  Haitham   were  surveyed. Data  wereobtained  on  methodof  usage and  results  of microbial examination. The  following points  were  reached.  1- Gram-negative bacteria  were the  most  common   ones,  especially   Pseudomonas  aero!{inosa  with38.9%1 of the total isolates. 2- Results of sensitivity  tests for antibiotics revealed that ofloxacin, ciprotloxacin. chlorampht:nicol , gentamycin and tobramycin were  effective against isolated  bacteria  from containers  and  preservative fluids of content  lenses.  3- Improper and non hygienic   measure::;    were   employed   especially  in   connection with keepi ng  the  preservative fluid and the containers tidy.